Novel Multi-Electromagnetic-Force-Compensation Weighing Cell With Axis-Symmetric Structure - Yoon, Kyung Taek; Lim, Hyunho; Bae, Jeong Hyun; Lee, Won Kyu; Kim, Dongmin; Choi, Young Man (IEEE/ASME Transactions on Mechatronics, 2022)
A Kibble balance for the realization of a redefined kilogram requires an ultraprecision weighing cell for measuring the difference between gravitational force and electromagnetic force. In this article, we propose a novel electromagnetic force compensation weighing cell for the Kibble balance at the Korea Research Institute of Standards and Science. To be compatible with the Kibble balance, the proposed weighing cell is designed axial symmetrically using a triple compound guide mechanism and a trilever mechanism based on a compliant mechanism. The weighing cell employs three independent mass measurement units to measure the test mass by dividing it, thereby improving the structural stability, weighing accuracy, and ground-tilt response. For a 1-kg test mass, the repeatability of the weighing cell was 0.74 mg in the air; it was improved to 0.20 mg when the zero-point drift was compensated. Finally, the experimental ground-tilt response of the weighing cell suggested that the ground-tilt angle can be estimated by observing the change in the compensating force of each mass measurement unit.
Keywords: Cell-be; Cell/B.E; Compliant mechanism; Electromagnetic force compensation; Electromagnetic force compensations; Forces measurements; Mass measurements; Optical device fabrication; Optical variable measurement; Weighing cell; Compliant mechanism; electromagnetic force compensation (EMFC); mass measurement; weighing cell